Early cannulation arteriovenous graft (Acuseal) versus standard arteriovenous graft in patients with end‐stage renal disease. Issue 4 (16th June 2021) - He, Jinyun; Zeng, Qianwen; Lang, Fen; Yang, Min; Liu, Zelong; Zeng, Lijuan; Liang, Ruiming; Wu, Shuwen; Tang, Qing
Abstract: Introduction: The use of Acuseal arteriovenous graft (AAVG) is spreading in end‐stage renal disease (ESRD) patients for its advantages in early cannulation. However, comparison of clinical outcomes between AAVGs and standard arteriovenous grafts (SAVGs) is limited. In this study, we compared the performance of AAVGs and SAVGs. Methods: Consecutive ESRD patients underwent prosthetic vascular access between October 2017 and May 2019 at a single center were identified. Patients were divided into AAVG group and SAVG group. Patients' demographics, perioperative characteristics, and clinical outcomes were collected. Primary, primary assisted, and secondary patency rates were compared using Kaplan‐Meier analyses. Postsurgery complications were compared using chi‐square test or the Fisher's exact test. Findings: A total of 304 arteriovenous grafts (AVGs) were implanted in 145 males and 159 females (mean age, 60.1 years; range, 20–91 years), comprising 143 AAVGs and 161 SAVGs. Median time to first cannulation was 3 days (interquartile range [IQR], 1–15 days) in the AAVG group and 30 days (IQR, 20–52 days) in the SAVG group ( P  < 0.001). Adjusted primary, primary assisted, and secondary patency at 12 months were not significant different between AAVGs and SAVGs ( P  = 0.911, P  = 0.945, and P  = 0.640, respectively). There was no statistical significance in regards to thrombosis (AAVG, 34.3%; SAVG, 26.1%; P  = 0.120) and infection (AAVG, 4.9%; SAVG, 2.5%; P  = 0.261) between the groups. Discussion: Acuseal grafts provide comparable patency, and complication rates to SAVGs, with less time to first cannulation from the graft implanted.